The Subject Role in the Application of Conceptual Metaphor - Hossein Razavian; Sedighe Tahmasebi (مطالعات زبانی و بلاغی)
Metaphor is a kind of inter-domain modeling that refers to understanding and expressing an abstract domain in a more concrete context. It is one of the most important issues in the cognitive field. Many researchers have confirmed that metaphor is conjured with our language. In preliminary studies, the frequency and the mode of metaphor application in different domains differed. That was why the authors decided to search the issue relying on the data in cookery and sport domains. So the two issues of cookery magazine and the two issues of sport magazine were selected randomly and all statements contained conceptual metaphors in these four magazines were extracted. The results and findings showed the metaphors’ multiplicity and diversity in sport domain and the little frequency and diversity of them in the cookery domain. Besides, based on the evidence obtained, the combat domain allocated highest prevalence and judging domain allocated the lowest in sport magazines. Extensive use of the metaphors in combat domain can be related to the spirit of competition in sport activities. In cookery magazines the highest prevalence belonged to the sphere domain and the size and direction domains allocated the lowest ones. Extensive use of the metaphors in cookery domain shows the significance of shape and form.